2010
DOI: 10.4314/nifoj.v25i2.50846
|View full text |Cite
|
Sign up to set email alerts
|

Organoleptic, minerals and vitamins’ evaluation of some Nigerian breads

Abstract: The organoleptic, minerals and vitamins' evaluation of some Nigerian breads were investigated. Five commonly consumed breads in Lagos, Nigeria, which were used for the study. These were Val-U, Nourish, Big-Treat, Unilag and Agege breads. These breads were purchased from reputable outlets within 24h of production. Organoleptic or sensory evaluation of the bread samples was carried out using 5-point hedonic scale and 20 panelists, who were regular consumers of bread. The appearance, odour, taste, texture and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
2
3
2
Order By: Relevance
“…Brown flat bread (A2-B2) named (Mufroud) had the highest content of Mg (57.46,74.42 mg/100 g), B2 with 74.42 mg/100 g differ significantly with all types of bread even with A2 as well which indicates the different extraction rate of brown flours from different milling plants. Similar results in the same types of bread reported [5][6][7] had Mg in the range of 110-130 mg/100 g, 128.2 mg/100 g and 55-305 mg/100 g respectively. These results showed that, this mineral is with lower content in almost all of Yemeni bread under study.…”
Section: Proteinsupporting
confidence: 89%
See 1 more Smart Citation
“…Brown flat bread (A2-B2) named (Mufroud) had the highest content of Mg (57.46,74.42 mg/100 g), B2 with 74.42 mg/100 g differ significantly with all types of bread even with A2 as well which indicates the different extraction rate of brown flours from different milling plants. Similar results in the same types of bread reported [5][6][7] had Mg in the range of 110-130 mg/100 g, 128.2 mg/100 g and 55-305 mg/100 g respectively. These results showed that, this mineral is with lower content in almost all of Yemeni bread under study.…”
Section: Proteinsupporting
confidence: 89%
“…The mineral composition data (Table 2) showed that, sodium content in all kinds of bread ranged from 58.16-555.6 mg/100 g. Mulwah with 10% of bran content (C2) contain the higher quantity of Na which may not be suitable for hypertensive individuals. Similar results in breads made of white wheat flour with sodium content of 217 mg/100 g, 548 mg/100 g and content of 207-304 mg/100 g respectively as reported 6,7,9 . Bread with reduced sodium has been marketed helps to maintain a healthy heart and circulation 19 .…”
Section: Fatsupporting
confidence: 85%
“…There were no significant differences in the mineral values among the bread samples. This is contrary to the reports of Ebuehi et al (2007) and Dooshima et al (2014) with bread samples in Lagos, Benue and Nassrawa metropolis in Nigeria.…”
Section: 2mineral Profilecontrasting
confidence: 99%
“…Mohammed (2009) determines the content of macro-and microelements in white flour bread and establishes comparable Zn values (0.61 mg.100 g -1 ). Ebuehi et al (2007) investigate the mineral content of the most commonly consumed bread in Nigeria and establish zinc content that is of the same order as those obtained in our study (0.3-0.6 mg/100 g). Higher values were published by Demirözü et al (2003) -10 mg.100 g -1 .…”
Section: Resultsmentioning
confidence: 63%